Spatially-distributed microbial enzyme activities at intact, coated macropore surfaces in Luvisol Bt-horizons. (May 2021) - Leue, Martin; Holz, Maire; Gerke, Horst H.; Taube, Robert; Puppe, Daniel; Wirth, Stephan
Abstract: Soil macropores serve as preferential pathways for water and solute transport as well as for root growth. They are often coated with organic material and known as "hotspots" of nutrient and C turnover. Differences in the SOM composition between macropores and soil matrix as well as between macropore types (biopores, cracks, pinhole fillings) imply potential differences in the microbial community composition and enzymatic activities. The objective of this work was to detect and assess the spatial distribution of enzyme activities related to C turnover, xylanase (XYL) and phenol oxidase (POX), and the composition of microbial communities in structural components of Luvisol Bt-horizons, developed from loess and glacial till. We applied conventional enzyme assays and phospholipid fatty acids (PLFA) analysis to study materials separated from different types of macropores and soil components as well as bulk soil samples. The spatial distribution of enzyme activities on surfaces of large soil core slices (20 cm in diameter) was quantified by soil zymography. Higher XYL activities were detected in separated burrow wall materials, clay-organic coatings, and pinhole fillings from both sites, as compared to the respective soil matrix or bulk soil samples. The XYL activities correlated with bacteria-specific PLFAs. POX activities were solely found increased for earthworm burrow walls from the loess-derived Bt-horizon, but not for burrows from till samples. Zymograms revealed particularly increased XYL activities at rooted earthworm burrows, emphasising evidence for hotspots of enzyme activity and C turnover. The zymography of POX was hampered by methodological restrictions. Highlights: Comparative analysis of enzyme activities at macropore surfaces. Xylanase and phenol oxidase assays using material from macropore walls and soil matrix. Zymography reveals xylanase but not phenol oxidase activities at macropore surfaces. Small-scale spatial distribution of enzyme activities in macroporous soils. Enzyme activities detected emphasise the role of macropores for C turnover processes.